Philosophy of Educational Management Problem Solving - Wijoyo; Sofwan Rijal (Konsultan Jurnal Ilmiah Indonesia, 2024)
This study discusses the Philosophy of Problem Solving in Educational Management. The purpose of this study is to find out how to deal with problems, stages of problem solving, strategies and solutions carried out in solving Educational Management Problems. This study is a qualitative study with data described descriptively regarding the use of libraries known as library research studies. The results obtained in this study are professional educational management, a manager is required to always be required to make changes towards being more dynamic. They must have a continuous spirit to seek new breakthroughs in order to produce changes that are developmental and perfecting, from conditions that are tense and worrying to conditions that are more dynamic, both physically and academically such as changes in the spirit of science, learning atmosphere and improving Islamic education management strategies.